Impact of pre‐analytical factors on blood‐based biomarkers of Alzheimer's disease. (20th December 2022) - Kurz, Carolin; Stöckl, Laura; Schrurs, Isabelle; Suridjan, Ivonne; Guersel, Selim; Bittner, Tobias; Jethwa, Alexander; Perneczky, Robert
Abstract: Background: Reliable blood‐based biomarkers (BBBMs) are urgently needed to allow for robust, cost‐effective pre‐screening of patients with suspected Alzheimer's disease (AD) before referral for detailed assessments. We evaluated the effects of storage time and temperature, plastic tube types, and freeze/thaw (F/T) cycles in fresh, never frozen and previously frozen whole blood (WB) and plasma. Effects of anticoagulants and tube transfer were only studied in previously frozen plasma. Method: WB samples from patients with clinically suspected AD were collected in ethylenediaminetetraacetic acid (EDTA) tubes and stored at room temperature (RT) or 4°C for ≤24hrs as WB or plasma. Separated plasma was transferred into polypropylene (PP) tubes to evaluate the effects of tube transfer and F/T cycles, or into low‐density polyethylene (PE‐LD) tubes to assess the effect of tube type. In addition to EDTA, lithium heparin (Li‐Hep) and sodium citrate (NaCit) tubes were used and effects of anticoagulants evaluated. Plasma levels of phosphorylated‐tau (pTau) 217, pTau181, amyloid‐β 1–42 (Aβ42), amyloid‐β 1–40 (Aβ40), apolipoprotein E4 (ApoE4), glial fibrillary acidic protein (GFAP), and neurofilament light chain (NFL) were measured using automated Elecsys ® prototype immunoassays (cobas e 601 analyzer; all Roche Diagnostics International Ltd). Result: For all BBBMs, pre‐analytical effects were comparable between fresh, never frozen and previously frozen samples. All BBBMs were stable for ≤24hrs at 4°C in WB and EDTA plasma; Aβ42, Aβ40, and ApoE4 were unstable if stored for >2hrs at RT. Up to five tube transfers, or two F/T cycles, and both tested plastic tube types were acceptable for all BBBMs. For all BBBMs, except Aβ42 and Aβ40, analyte levels were comparable between EDTA, Li‐Hep, and NaCit tubes. Aβ42 and Aβ40 were most sensitive to pre‐analytical sample handling and the effects could only be partially compensated by the Aβ42/Aβ40 ratio. Conclusion: We provide recommendations for an optimal handling protocol for blood collection and sample handling for analysis of BBBMs for AD based on measurement in fresh samples (Figure ): WB and EDTA plasma should be stored at 4°C for ≤24hrs, while storage at RT should be avoided or limited to 2hrs maximum.